Develop power amplifier and mixer for 5G transceiver - Fan,Guanghao (Nanyang Technological University, 2023)
With the rapid development of 5G communication system, the industrial demand for high-frequency and high-speed electronic components is increasing. The great advantages of 5G are high speed, low power consumption, low delay, reconstruction security and other aspects. These advantages lead to the need for better performance of the corresponding hardware RF device. The core RF device in 5G communication technology is mainly the transceiver, and the core block in the transceiver is the power amplifier (PA) and mixer. PA and mixer have been extensively studied by researchers from various countries, and a variety of topologies have been designed. Not only that, the production process of RF devices is also constantly developing. At present, the GaN process has better performance under high frequency characteristics. With the continuous advancement of common prosperity, people's increasing demand for material level is met, and the demand for the construction of the spiritual world is also gradually increasing. Human beings have entered the information age, and mobile network has become an important part of people's needs for the construction of the spiritual world. The demand for wireless communication products is gradually increasing, and an increasing demand for channel capacity and communication rate is put forward. In order to meet the growing communication needs of people, the frequency of wireless communication system is more and more high, the modulation technology of the signal is constantly enriched, and communication equipment is required to provide better performance. As one of the important components of RF communication system, power amplifier greatly affects the overall performance of the system. Therefore, in order to improve the performance of the transceiver system, the in-depth study of RF device power amplifier and mixer is imperative.